Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan Ipa Kombinasi Model PBL, MIND MAPPING dan NHT - Masyitah; Suhaimi (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem in this study is the low activity and student learning outcomes in science learning. This study aims to describe teacher activities, analyze student activities, and improve student learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research conducted in 4 meetings. The research subjects were 12 grade IV student at Teluk Dalam 12 Elementary School, Banjarmasin. The type of data in this study uses qualitative and quantitative data. Qualitative data were obtained from observing teacher activities and student activities. Quantitative data was obtained through individual written test meansuremen techniques. The benchmark for research success is 80% or a value of 70%. Based on the data findings and result of this study, it can be concluded that teaching and learning activities using the combined learning model of Problem Based Learning, Mind Mapping and Number Head Together are able to increase student activity and learning outcomes.